The healthcare system in Africa: the case of guinea - Camara, Mohamed Elmahady; Camara, Ansoumane Yassima; Camara, Nafissatou (International Journal Of Community Medicine And Public Health, 2017)
Background: The aim of this article is to review the health system of Guinea from its past period to its recent period. The article gives an overview of the general situation of the country. It presents the political; economic, social situation of Guinea. It briefly addresses the country’s situation before its independence and goes on to describe its health situation from its independence on October 2nd, 1958 to 2014. Methods:This article is both retrospective and prospective. It highlights some epidemic diseases such as the Cholera, which has become almost endemic in the country. It also describes the current burden of diseases in the country. Results: The environment is a factor contributing to the health issues in the Republic of Guinea; among others, we can list unsafe water, hygiene, and excreta disposal; urban air pollution; and indoor smoke. This article shows that the current health issues in Guinea are due to the above factors. The Ebola outbreak is an illustration of the Global Health problem that started in Guinea in 2014. Conclusions:At the end of this article, changes and improvements to the healthcare system in the Republic of Guinea are proposed.